Changings in Women’s Role in System of Labour Relations during Great Patriotic War (based on Materials of Stalingrad Region) - A. V. Lipatov (Научный диалог, 2019)
The fundamentals of the social policy of the Soviet state in relation to women, the mechanisms of formation of the contract of “working mother” are considered. The relevance of the study is determined by the change in the position of women in Soviet society in the war and the first postwar years, when the status of “working mother” is formed at the official level. The authors analyze the system of social and legal protection of working women. Attention is paid to the consideration of key legislative acts: the decisions of the government of the USSR and the leadership of the Stalingrad region, aimed at protecting the rights of working women during the Great Patriotic war, and also shows the specific activities of the authorities aimed at involving women in productive activities. The mechanisms that make it possible to combine motherhood with work in industry, agriculture, construction and economic recovery after the Stalingrad battle are analyzed. The question is raised about the mechanisms of social protection of working women: improvement of living conditions, allocation of places in nurseries and kindergartens, exemption from labour mobilization of pregnant and nursing mothers, training and retraining. The authors draw conclusions about the significant role of “working mother” contract in wartime, analyze the effectiveness of the measures taken by the government on the basis of the study of legislation, a wide range of sources and statistical materials.